2022
DOI: 10.21203/rs.3.rs-1862013/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomics of differences in thermal plasticity associated with selection for an exaggerated male sexual trait

Abstract: BackgroundThe information about the magnitude of between-individual differences in thermal plasticity and identification of the underlying molecular mechanisms are key to understand the evolution of thermal plasticity. In particular, genes underlying variation in the physiological response to temperature can provide raw material for selection acting on plastic traits. Using RNAseq, we investigate the transcriptional response to temperature in males and females from the bulb mite populations selected for the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Nonetheless, these results suggest that despite scramblers being more burdened with deleterious mutations compared to fighters (Łukasiewicz et al 2020, this does not influence their fertility under thermal stress. One possible explanation for why we did not observe any morph-specific difference in TFL or TSF is that there are limited morph-specific changes in gene expression when exposed to higher temperatures (Plesnar-Bielak et al 2022), suggesting that differences between fighter and scrambler plastic responses to thermal stress may be limited. We also find no support for the view that bearing costly weaponry amplifies the costs of thermal stress in a way that also influences fertility, or indeed mating rates.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Nonetheless, these results suggest that despite scramblers being more burdened with deleterious mutations compared to fighters (Łukasiewicz et al 2020, this does not influence their fertility under thermal stress. One possible explanation for why we did not observe any morph-specific difference in TFL or TSF is that there are limited morph-specific changes in gene expression when exposed to higher temperatures (Plesnar-Bielak et al 2022), suggesting that differences between fighter and scrambler plastic responses to thermal stress may be limited. We also find no support for the view that bearing costly weaponry amplifies the costs of thermal stress in a way that also influences fertility, or indeed mating rates.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that both spermatogenesis and oogenesis are sensitive to temperatures that do not cause complete sterilisation. The expression of a large number of genes has been shown to be altered in R. robini due to exposure to different thermal conditions (Plesnar-Bielak et al 2022), and it is possible that expression of genes involved in pathways associated with both oogenesis and spermatogenesis have been altered. We found that these thermal effects on male and female fertility appear to be additive, as the greatest declines in reproductive output occur when both males and females are heat stressed.…”
Section: Discussionmentioning
confidence: 99%
“…We downloaded the bulb mite genome’s predicted gene annotation from ORCAE (Parrett et al, 2022; Sterck et al, 2012), https://bioinformatics.psb.ugent.be/gdb/Rhizoglyphus_robini), which contains an unexpectedly high number of predicted genes (60,310 genes), suggesting the presence of pseudogenes or gene prediction errors. To refine the dataset, we excluded genes with expression levels below 1 FPKM, based on expression data from Plesnar-Bielak et al (2022). This filtering retained 27,363 genes mapped to chromosomes.…”
Section: Methodsmentioning
confidence: 99%